2019
DOI: 10.1101/835561
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Genome of the Charophyte AlgaPenium margaritaceumBears Footprints of the Evolutionary Origins of Land Plants

Abstract: 30The colonization of land by plants was a pivotal event in the history of the biosphere, and yet the 31 underlying evolutionary features and innovations of the first land plant ancestors are not well 32 understood. Here we present the genome sequence of the unicellular alga Penium margaritaceum, 33 a member of the Zygnematophyceae, the sister lineage to land plants. The P. margaritaceum 34 genome has a high proportion of repeat sequences, which are associated with massive segmental 35 gene duplications, likel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 158 publications
1
7
0
Order By: Relevance
“…By contrast, Zygnematophyceae zygospores contain algaenan that differs from pollen grains in its chemical position and the biochemical pathway (acetate-malate pathway) leading to its production (97). Furthermore, to our knowledge, the presence of type III PKS-like enzymes in the genomes of Charophyta is not reported with the exception of Penium margaritaceum (36). The adaption of a sporopollenin-containing protecting spore wall is considered a synapomorphy of the embryophytes to colonize the land, but appears to be pre-adaptive given that it is present in the Charophyceae, the proposed sister group to the embryophytes (7,(94)(95)(96)98).If LAP5/6 evolved first, the syntenic clusters 1/27 and/or 3/11 duplicated and formed the cluster that later the syntenic cluster that contain 'R-4-C'-type PKS genes followed by a loss of synteny between the clusters 1/27 and 3/11.…”
Section: Possible Evolutionary Route Of the Pks Superfamily Suggestementioning
confidence: 81%
See 1 more Smart Citation
“…By contrast, Zygnematophyceae zygospores contain algaenan that differs from pollen grains in its chemical position and the biochemical pathway (acetate-malate pathway) leading to its production (97). Furthermore, to our knowledge, the presence of type III PKS-like enzymes in the genomes of Charophyta is not reported with the exception of Penium margaritaceum (36). The adaption of a sporopollenin-containing protecting spore wall is considered a synapomorphy of the embryophytes to colonize the land, but appears to be pre-adaptive given that it is present in the Charophyceae, the proposed sister group to the embryophytes (7,(94)(95)(96)98).If LAP5/6 evolved first, the syntenic clusters 1/27 and/or 3/11 duplicated and formed the cluster that later the syntenic cluster that contain 'R-4-C'-type PKS genes followed by a loss of synteny between the clusters 1/27 and 3/11.…”
Section: Possible Evolutionary Route Of the Pks Superfamily Suggestementioning
confidence: 81%
“…The PKSs from Ectocarpus siliculosus fall within the range of generic PKS sequences found in These findings suggest that a lateral gene transfer of type III PKS, possibly by an ancestral actinobacterium, occurred following the separation of the diatoms from other members of the Ochrophyta, but before the brown algae diverged from the Pelagophytes and Dictyochophytes(51). Similarly, genes of other pathways, including the genes for mannitol, alginate and hemicellulose biosynthesis, are present in brown algae but absent in diatoms, suggesting a lateral gene transfer from an ancestral actinobacterium to Ectocarpus siliculosus(51,56,57).It was previously stated that land plants originated from the Streptophytes of the Penium margaritaceum was reported to contain eleven copies of type III PKS(36). This indicates that type III PKS appeared earliest with the Zygnematophyceae, but not with the earlier appearing…”
mentioning
confidence: 99%
“…Nevertheless, it was suggested that the majority of the orthologs of land plant auxin pathways were found in charophytes, but absent in chlorophytes. Indeed, recently published charophyte genomes confirmed the presence of orthologs of various pathways that were earlier thought to be specific to land plants (Jiao et al, 2019;. In Chapter 3, we also found that the single homologs of auxin biosynthetic gene families (TAA and YUC) were found in charophytes but not in the chlorophytes.…”
Section: Phylogeny Construction and Visualizationsupporting
confidence: 67%
“…On the other hand, two-component histidine kinase signaling components of cytokinin and ethylene pathways evolved prior to land plants, representing system that is more ancient than the nuclear auxin pathway (Bowman et al, 2017;Jiao et al, 2019;. In contrast, despite the presence of some ABA synthesis pathway components in charophytes, the ABAdependent responses were found only in land plants and further enhanced in vascular plants by gaining additional receptors .…”
Section: Gh3mentioning
confidence: 99%
“…This suggests the absence of the functional canonical auxin biosynthetic pathway in K. nitens and implies that this pathway is a land plant innovation [ 23 ]. Recent projects on the genome sequencing of charophytes Penium Margaritaceum (Zygnematales) [ 57 ], Chara braunii [ 57 , 58 ], and Nitella [ 28 ] (Charophyceae) support this hypothesis: neither TAA nor YUCCA homologs were identified in these genomes. These data are consistent with experimental results by Ai et al [ 59 ], who demonstrated that Klebsormidium TAA homologs could not restore the wild-type phenotype of taa mutants in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%